ANALYSIS OF THE USE OF ALLEGORY IN GEORGE ORWELL’S “ANIMAL FARM” - Rodhiatammardiyah, Bella; Rabbani, Beril; Putra, Muhammad Dzaky Maulana; Nurholis, Nurholis (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
George Orwell's Animal Farm is a highly satirical allegory of the Russian Revolution and the rise of the totalitarianism under Joseph Stalin. Through the revolt of farm animals against their owner, Mr. Jones, Orwell criticizes the corruption of revolutionary ideals, illustrating how a noble intention can turn into an oppressive regime. The characters in the novel symbolize key figures in history, such as Napoleon as Stalin and Snowball as Trotsky, allowing readers to explore the power dynamics and betrayal. The analysis uses formalist and a sociological method to examine how allegorical elements, propaganda, and character portrayals reflect broader social and political themes. In the end, Animal Farm emphasizes the dangers of absolute power and the importance of accountability in leadership.